Validation of a novel clinical tool for monitoring distal limb stiffness - Jacklin, Benjamin D.; Hanousek, Katherine; Gillespie, Sabrina; Liedtke, Anna; Tucker, Rachel; Fiske-Jackson, Andrew; Smith, Roger K. (Frontiers in Veterinary Science, 2024)
Objective: To validate a novel technique to measure limb stiffness in a clinical setting. Animals: Three horses and three ponies owned by the Royal Veterinary College Procedures: Limb stiffness indices for both forelimbs were first derived using the gold standard of kinematic analysis. Using the same animals, limb stiffness indices were then calculated using portable floor scales to record weight and an electrogoniometer to record changes in metacarpophalangeal joint angle. The two techniques were then assessed for correlation and repeatability. Results: Repeatability of limb stiffness measurement using the novel clinical tool was considered to be good based on a small coefficient of variation (5.70%). Correlation of limb stiffness as derived by both methods was high (r=0.78, p<0.01). Limb stiffness was positively correlated with the mass of the subject (r=0.85, p<0.01), with heavier horses having greater limb stiffness. Clinical relevance: This study has compared a novel method to measure distal forelimb stiffness non-invasively in a clinical setting to kinematic analysis in six equids. It has demonstrated that limb stiffness increases in a linear fashion with body mass consistent with the role of forelimbs providing energy storage. Because in-vivo limb stiffness has been shown previously to alter with injury to the superficial digital flexor tendon, it is hypothesised that this technique will offer a practical technique for the clinician to assess limb stiffness in clinical cases. Further work will be necessary to determine its clinical usefulness in such cases.